Hubungan Usia, Masa Kerja Dan Kelelahan Kerja Dengan Keluhan Gangguan Otot Rangka Akibat Kerja (GOTRAK) Pada Pekerja PT. X - Rochmania, Aidina; Sunaryo, Merry; Al Isyrofi, Atik Qurrota A Yunin; Wijaya, Satriya (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Muscleskeletal complaints are damages to ligaments, joints, tendons, nerves, muscles, and cartilage can occur when muscles continuously bear static loads. These complaints often occur in workers, especially those in the winding department. The purpose of this study is to determine factors related to work-related musculoskeletal complaints in employees of PT. X. This research uses a cross-sectional study design with a quantitative descriptive approach. Sampling technique was carried out using proportional stratified random sampling with 78 workers. Bivariate analysis using Spearman test was conducted by observing the correlation coefficient values. There is a correlation between age and musculoskeletal complaints (GOTRAK) which has a fairly significant level of correlation in the neck, shoulders, upper back, lower back, and legs. There is a correlation between length of employment and GOTRAK complaints which has a fairly significant level of correlation in the shoulders, hands, lower back, knees, and legs. Meanwhile, in the neck and upper back, there is a moderate level of correlation. There is a correlation between the level of work fatigue and GOTRAK complaints which has a fairly significant level of correlation in the shoulders, knees, and legs. In the neck, hands, and lower back, there is a moderate level of correlation. Whereas in the upper back, there is a strong level of correlation. It is recommended for workers to improve their working methods to reduce the risk of complaints while working and to stretch their muscles, especially in the hands, back, and legs for fifteen minutes before starting work.